Miosite Orbitária - Aguiar, T (2011)
Orbital myositis is a subgroup of the nonspecific inflammatory syndrome or orbital pseudotumor and is characterized by a primary inflammation of extraocular muscles. The authors describe a 70-year-old patient with acute proptosis, ocular pain and right ophthalmoplegia, whose orbital computed tomographic scan showed enlargement of the homolateral extraocular muscles. Clinical presentation and complementary tests were compatible with the diagnosis of orbital myositis however, because of the particular aspects, which included retinal central vein occlusion, optic nerve lesion, distension of the superior ophthalmic vein and the homolateral cavernous sinus, the differential diagnosis with cavernous sinus pathology and thyroid ophthalmopathy was considered. The importance of a rapid diagnosis and treatment is stressed.